Foundations of WPF: An Introduction to Windows Presentation Foundation - Moroney, Laurence (Apress, 2012)
The Windows Presentation Foundation is one of the new “foundations” being introduced by Microsoft in .NET 3.0, along with the Windows Communication Foundation and the Windows Workflow Foundation. The Windows Presentation Foundation is a vital component to the future of application development, allowing developers to take control of the sheer power that is available at the desktop to develop rich, interactive, media-enhanced user interfaces. My first professional programming experience was to model the unproductive text-based interface used for programming and configuring surveillance systems as a Windows-based graphical user interface using Visual Basic 3.0. The productivity enhancement that this brought allowed large-scale systems to be configured in minutes instead of in hours or days. Going from Windows user interfaces to rich-media user interfaces using Windows Presentation Foundation will start yielding the same productivity and user experience leaps. This book is based on the July Community Technical Preview of Windows Presentation Foundation, and by the time the book is in your hands, the technology may be slightly different—this is a Foundations book, after all; it’s intended to teach you the fundamentals of the technology and to take the edge off the learning process. I hope you have as much fun reading and using it as I had writing it!